DESIGN, SIMULATION AND ANALYSIS OF WIRELESS POWER TRANSFER PERFORMANCE FOR CONCENTRIC COIL USING ANSYS MAXWELL AND MATLAB SIMULINK - Beket, Mereke (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This work presents the design of an inductive power transfer (IPT) system with concentric coil geometry with simulation and analysis carried out within MATLAB and ANSYS environments. The efficiency in the simulated system was 77.63% under perfect alignment, decreasing to 75.44% and 67.74% when there was 2 cm and 4 cm misalignment, respectively. Experimental verification in air and salt water was used to show system reliability and achieved efficiencies of 71.47% and 74.57%, respectively. In misalignment tests, the efficiency decreased from 69.22% to 30.03% in air and from 62.47% to 50.55% in salt water as coil displacement was increased. Although performance decreased with complete misalignment, the system remained stable for partial displacement, indicating towards its suitability for dynamic coil position settings, i.e., underwater deployments. With a consideration for low-power operation, this work opens doors for the design of future efficient and high-power IPT systems.
Keywords: Wireless Power Transfer; IPT; MATLAB Simulink; ANSYS Maxwell 3D; Concentric Coils; type of access: open access